Localization of QTL for resistance to Pyrenophora teres f. maculata, a new wheat pathogen - Uranga, Juan Pablo (2020)
The fungus Pyrenophora teres causing disease symptoms similar to P. tritici-repentis was recently detected on wheat in Argentina. After confirmation by molecular studies the pathogen was identified as P. teres f. maculata, part of a complex of leaf spots that affect wheat and other cereal crops. The objective of this work was to characterize the virulence and identify QTL conferring resistance to two isolates of P. teres f. maculata (Ptm) in a collection of 110 spring wheat genotypes previously assembled for association mapping and genotyped with 2836 DArT markers. Two isolates of Ptm (PT2047 and PT2050) were used in field experiments. To find marker-trait associations (MTAs) a mixed linear model implemented in TASSEL 5.1 software was used. Considerable phenotypic variation in disease severity was observed at the seedling and adult stages, and some accessions were resistant to both isolates over 2 years. Twelve MTAs identified with nine markers were significantly associated with resistance. The nine markers were distributed over seven chromosomal regions on 6 of the 21 wheat chromosomes. These QTL were novel since this is the first study to identify genomic regions associated with resistance to Ptm in wheat. Wheat genotypes with moderate to high levels of resistance to P. teres f. maculata were identified and will be useful in breeding programs.